A study on video performance of multipoint-to-point video streaming with multiple description coding over ad hoc networks - Utsu, K.; Chow, C.; Ishii, H. (John Wiley & Sons, 2010)
Supporting multimedia applications over wireless networks has become a very active research topic recently because video applications are forecast to receive high demand in future wireless networks, such as ad hoc networks. However, enabling video transmission over wireless ad hoc networks is more challenging than over other wireless networks due to node mobility, interference, and the absence of a supporting in frastructure. This paper addresses the problem of video transmission over ad hoc networks. We propose to combine Multiple Description Coding (MDC) with multiple source transport (Multipoint-to-Point transfer: MP2P) in order to maintain smooth video streaming over wireless ad hoc networks. In this paper, we describe a comprehensive simulation and test bed experiment designed to show the effect of the proposed MP2P video transfer with MDC for two description cases of video streaming over wireless ad hoc networks. The results Show that the proposed mechanism successfully improves video transfer performance in terms of video packet reachability and throughput. (c) 2009 Wiley Periodicals, Inc. Electr Eng Jpn, 170(4): 43-50, 2010; Published online in Wiley InterScience (www.interscience.wiley.com). DOI 10.1002/eej.20999